Transparency of public service principles in Amantelu Village, Sirimau District, Ambon City - Simatauw, H.E (International research journal of management, IT and social sciences, 2021)
This research was carried out at the Amantelu Village Office, Sirimau District, Ambon City, using a single variable (monovarietal) by making critical informants, primary informants, and additional informants, with four focuses and a description of the focus. However, employees here always prioritize transparency in public services to citizens. Find out everything related to public services, such as requirements, procedures, costs, and the like; access is given as comprehensively as possible in the process of public services. Regarding the issue of employee commitment to public services, it is still not running as expected. This can be seen in the lack of or inconsistency in applying the principles of public services to citizens, especially those related to convenience and cost. In carrying out public services at the Amantelu Village Office, the community still has to meet various convoluted requirements to get services.